2020
DOI: 10.1007/s40820-020-00494-2
|View full text |Cite
|
Sign up to set email alerts
|

Hot-Casting Large-Grain Perovskite Film for Efficient Solar Cells: Film Formation and Device Performance

Abstract: Organic–inorganic metal halide perovskite solar cells (PSCs) have recently been considered as one of the most competitive contenders to commercial silicon solar cells in the photovoltaic field. The deposition process of a perovskite film is one of the most critical factors affecting the quality of the film formation and the photovoltaic performance. A hot-casting technique has been widely implemented to deposit high-quality perovskite films with large grain size, uniform thickness, and preferred crystalline or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 112 publications
0
34
0
Order By: Relevance
“…Chemical methods include solvent and/or additive engineering, and so on. [87][88][89][90] The corresponding performances of PSCs prepared by the scalable blade-coating method are summarized in Table 2.…”
Section: Recent Advances In Blade-coated Perovskite Solar Cellsmentioning
confidence: 99%
“…Chemical methods include solvent and/or additive engineering, and so on. [87][88][89][90] The corresponding performances of PSCs prepared by the scalable blade-coating method are summarized in Table 2.…”
Section: Recent Advances In Blade-coated Perovskite Solar Cellsmentioning
confidence: 99%
“…7 In such PSCs, there exist plenty of defects on the surface of the perovskite film, which can cause serious carrier recombination and thus results in energy loss. [8][9][10] The defects can also induce severe perovskite/ Spiro-OMeTAD interface instability, and hence leads to rapid device degradation during storage or under operation. 11,12 A series of different materials, including PbI 2 , alkylammonium halogen salts, wide-bandgap inorganic oxides and lewis acid/bases, have been introduced to passivate the surface defects of the perovskite film.…”
Section: Introductionmentioning
confidence: 99%
“…In the standard architecture of the planar PSCs (ITO/ETL/perovskite/HTL/Au), the most widely used HTL (ETL) is Spiro‐OMeTAD (SnO 2 ) 7 . In such PSCs, there exist plenty of defects on the surface of the perovskite film, which can cause serious carrier recombination and thus results in energy loss 8‐10 . The defects can also induce severe perovskite/Spiro‐OMeTAD interface instability, and hence leads to rapid device degradation during storage or under operation 11,12 …”
Section: Introductionmentioning
confidence: 99%
“…There are several crystallization control methods including hot‐casting technique, [ 6,8–11 ] solvent engineering, [ 12–15 ] antisolvent method, and so on. [ 16–20 ]…”
Section: Introductionmentioning
confidence: 99%
“…However, the thermal annealing process governs the crystallization process, starting from the nucleus of the as‐prepared perovskite film. [ 16 ] Nie et al first reported the strong correlation between the substrate temperature and device performance during the hot‐casting process. They demonstrated that high substrate temperature could promote the crystal growth and significantly improve charge mobility by reducing the grain boundaries and the defect density.…”
Section: Introductionmentioning
confidence: 99%